2023
DOI: 10.3390/d15101050
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of Inland Wetlands: Important Roles in Mitigation of Human Impacts

Igor Zelnik,
Mateja Germ

Abstract: Inland wetlands are one of the most vulnerable ecosystems on Earth and have one of the highest rates of decline in surface and biodiversity [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 22 publications
0
0
0
Order By: Relevance
“…Many freshwaters in Slovenia belong to the most endangered habitats (ARSO, 2021). It was recently reported that inland wetlands are highly vulnerable ecosystems on Earth and have one of the highest rates of decline in surface and biodiversity (Zelnik & Germ, 2023). The Krka River is threatened as far as its suitable habitats for aquatic organisms are concerned.…”
Section: Macrophytesmentioning
confidence: 99%
See 1 more Smart Citation
“…Many freshwaters in Slovenia belong to the most endangered habitats (ARSO, 2021). It was recently reported that inland wetlands are highly vulnerable ecosystems on Earth and have one of the highest rates of decline in surface and biodiversity (Zelnik & Germ, 2023). The Krka River is threatened as far as its suitable habitats for aquatic organisms are concerned.…”
Section: Macrophytesmentioning
confidence: 99%
“…Rivers created important places where numerous people settled in ancient times and the first great civilizations began by rivers such as Huang He (Yellow River), Indus, Nile, Tigris, and Euphrates (Macklin & Lewin, 2015). These civilizations used rivers to supply them with water, food, and building materials (Zelnik & Germ, 2023). Rivers and their watersheds comprise some of the largest inland macrosystems on earth (Thorp et al, 2023), offering a habitat for many organisms and influencing the area's microclimate conditions.…”
Section: Introductionmentioning
confidence: 99%